Interrogating the practice of curricular contextualization the dynamics of school and community band music education - Guadalupe, Jocelyn Timbol
The study problematizes music curricular contextualization policy in the Philippines K to 12 curriculum. Inquiry is made into the negotiations, constraints, and forces mediating policy enactment as the dynamics of formal, informal, and non-formal music education interact showing practices that reconfigure content, performance, and meaning in the music curriculum. The ethnographic study analyzes the experiences of 12 selected music teachers and their 23 students from long-standing community band traditions in Taytay, Riza, Philippines. An examination of official music curriculum documents and contextualization memoranda provides policy data complementing band archival research and informal observation from 2017, interviews, focused group discussions, surveys, classroom and community band observations conducted within seven months (September 2019 - March 2020). Using policy as practice of music curricular contextualization as frame, the findings reveal music teachers' negotiations: music listening selections, immersion and integrative teaching strategies; mediating forces: teachers' policy understanding and music content knowledge; and constraints: standardized examinations and inadequate school music resources. Interviews with junior community band students highlight musical agency in the dynamics of power in the classroom. junior community band members' use of musical funds of knowledge from band during class discussions exemplifies agency leading toward cultural production. Recommendations include community dialogue, adaptations of community band practices in class, and a paradigm shift toward student-led learning and assessment. A proposed music curricular contextualization model in the Philippines integrating perspectives within policy framework signifies the complex nature of music contextualization and the pivotal role of qualified music educators.